PENDEKATAN METODOLOGI FEATURE DRIVEN DEVELOPMENT PADA APLIKASI E-COMMERCE (STUDI KASUS CV. MEGAJAYA) - Mutia Sari Zulvi; Rika Perdana Sari; Yuli Fitrisia (ABEC Indonesia, 2021)
e-Commerce is a trading activity carried out through intermediary web pages on the internet. One of the e-Commerce applications is Business to Business (B2B). Called B2B because of transactions between companies. One company that uses B2B principles is CV Mega Jaya with business processes with simple scale and complexity. In marketing various kinds of fertilizers, CV Mega Jaya only uses brochures that are passed on from certain people to others. Another thing is seen from the ordering side, CV Mega Jaya only uses communication tools or meets in person to order fertilizer. Therefore, e-commerce applications are needed to deal with these problems. In building an E-Commerce application, it takes a method that supports smooth application development called SDLC (System Development Life Cycle). One type of SDLC used is Agile. Agile Methods can accept additional requirements even though they are in the process of being built or completed without going back to the initial stage. Agile used is Feature Driven Development (FDD) which prioritizes features and design and scheduling is directed by features. FDD is suitable for applications that have a B2B case. The result of this research is that the application can be completed on time. This app underwent 1 functional change in features after stage 1. And experienced 1 additional feature (10% of coverage, time and cost). It would be better if FDD is used by more than 1 experienced person (in a team).Keywords: e-Commerce, Business to Business (B2B), CV Mega Jaya, System Development Life Cycle (SDLC), Feature Driven Development (FDD))